Inisiasi Penerapan Purcell Principle oleh Mahkamah Konstitusi dalam Pengujian Undang-Undang terkait Pemilihan Umum - Dian Agung Wicaksono; Garuda Era Ruhpinesthi (Jurnal Konstitusi)
The Constitutional Court (MK) Decision Number 90/PUU-XXI/2023 has sparked discourse regarding the timing of its legal effects, whether for the 2024 or 2029 General Election (Pemilu). According to the Purcell Principle, courts should not rule on cases once the election process has begun. This study aims to answer two questions: (a) How compatible is the Purcell Principle with MK’s authority in judicial review? (b) How has MK initiated the application of the Purcell Principle in judicial review of election-related laws during the election stages? This normative juridical study uses relevant secondary data. The findings show that the Purcell Principle is compatible with MK’s judicial review authority since both apply prospective legal effects. MK previously applied the Purcell Principle in Decision Number 14/PUU-XI/2013. Over time, MK no longer used it, but in Decision Number 116/PUU-XXI/2023, it “applied” the principle by setting conditional constitutionality for the 2029 election.